1992
DOI: 10.1016/0736-5748(92)90052-2
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal morphine exposure alters peptidergic development in the striatum

Abstract: It has been reported that perinatal exposure to opiates affects mRNA synthesis, body growth and brain development in mammals, including humans. We have observed that morphine administration in drinking water during the perinatal period alters peptide development in the striatum of the rat. There is a marked increase in substance P and met-enkephalin content, the latter is maintained even at 30 days postnatally. The transient increase or earlier maturation of substance P content is correlated by a more precocio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
11
0

Year Published

1993
1993
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…After weaning, the opiate dosage to the pups, now separated from their mothers, was markedly reduced, but no signs of withdrawal such as respiratory depression were observed. As reported previously, body growth was reduced by 20% in animals perinatally exposed to morphine (Tenconi et al, 1992). cortex was similar among all the experimental groups at 7 days; however, it was significantly higher in the salinetreated lesioned animals at 8 weeks of life (Figs.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…After weaning, the opiate dosage to the pups, now separated from their mothers, was markedly reduced, but no signs of withdrawal such as respiratory depression were observed. As reported previously, body growth was reduced by 20% in animals perinatally exposed to morphine (Tenconi et al, 1992). cortex was similar among all the experimental groups at 7 days; however, it was significantly higher in the salinetreated lesioned animals at 8 weeks of life (Figs.…”
Section: Resultssupporting
confidence: 75%
“…These data suggest the direct or indirect implication of the endogenous opioid system in the modulation of growth and development of the nervous system. Previous studies performed in our laboratory showed that perinatal exposure to morphine affects met-enkephalin (ME) and substance P (SP) innervation of the striatum (Tenconi et al, 1992). The peptidergic changes occur also in other brain areas and are accompanied by reduced expression of synapsin I mRNA, suggesting that perinatal morphine treatment affects synaptic development and maturation in the brain (Di Giulio et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of morphine drunk by the single pups was smaller, but no signs of withdraw1 were observed. We also monitored body growth, which declined in the morphine groups by about 20 percent, confirming the detailed report of Tenconi et al (1992).…”
Section: Resultsmentioning
confidence: 87%
“…and perfused with 4% paraformaldehyde-0.5% glutaraldehyde mixture, then the lumbar cord was dissected out postfixed overnight with the same fixative. Specimens were then sectioned with a Cambridge vibratome and stained following procedures previously published (Di Giulio et al, 1985, 1989.The oligonucleotide complementary of pre-proenkephalin (NEP 502) was labelled at the 3' end with terminal deoxynucleotidyl transferase, as was previously described (Tenconi et al, 1992). For the neurotrophin in situ hybridization studies, we used cDNA probes corresponding to the 0.77 kb fragment of the rat gene for NGF, that was subcloned at the Sma I site of pBluescript (M13 +); and cDNA probes corresponding to the 3.4 kb fragment of the rat gene for p75 fast NGFR subcloned at EcoR I-Hind 111 sites of pUC19.…”
mentioning
confidence: 99%